Bimbingan Firman Tuhan Kepada Jemaat GKSI Yesyurun Senyamuk Tentang Pentingnya Ibadah - Helsina Koen; Haleti Hulu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
A number of congregations at GKSI Yesyurun Senyamuk show a tendency to not be active in worshiping regularly. This phenomenon needs serious attention so that the congregation can once again appreciate and feel the importance of worship in their lives. One of the main causes of inactivity in worship is the busyness of daily life which increasingly dominates the congregation's attention. This busyness is often a reason that is considered valid for not attending church services. Meanwhile, the method used is qualitative based on direct observation of the phenomena that occur at GKSI Yesyurun Senyamuk. Apart from that, guidance was provided on the word of God to the GKSI Yesyurun Senyamuk congregation, explaining